How Do Radical Left Parties Frame the Nation? A Comparison Between Greece, Spain and France - Karavasilis, Lazaros; Custodi, Jacopo; Chazel, Laura (PARTECIPAZIONE E CONFLITTO, 2024)
The trajectory of radical left parties during the 2010s presents a complex facet of contemporary European party politics. The decline of traditional social-democratic parties has at times facilitated the rise of political formations positioned to their left, addressing issues increasingly neglected by the mainstream Left. While scholars have extensively explored the radical Left's relation to austerity politics, EU institutions, populism, and political strategies, less attention has been given to how these parties frame the concept of the nation and articulate national belonging. This paper seeks to address this academic gap by comparing the three most prominent radical left parties in Europe during their peak: SYRIZA in Greece, Podemos in Spain, and La France Insoumise in France. Through discourse analysis, this study focuses on how these parties employ a form of left-wing patriotism to integrate national elements into their discourses. Ultimately, this paper aims to shed light on a frequently overlooked aspect of the radical left party family through a comparative analysis.